Triple Negative Breast Cancer Characteristics Based on Basal-like and Non-Basal-like Subtypes - Fifi Akwarini; Trinugroho Heri Fadjari; Bethy Suryawathy Hernowo (International Journal of Integrated Health Sciences, 2019)
Objective: To observe triple negative breast cancer (TNBC) characteristics in three hospitals located in Bandung based on basal-like (BL) and non-basal-like (NBL) subtypes.Methods: This was a cross-sectional study which used descriptive categorical data from medical records and paraffin blocks of TNBC patients treated in Dr. Hasan Sadikin General Hospital, Bandung; Borromeus Hospital; and Santosa Hospital Bandung Central in the period of January 1, 2012–December 31, 2016. The subjects of the study were 57 TNBC patients. The data collected in the study based on medical records were age, tumor size, histopathological images, severity, and immunohistochemical data. The paraffin blocks of the patients based on the completed medicals records were investigated through examinations of immunohistochemichal cytokeratin (CK) 5/6 expressions and epidermal growth factor receptor (EGFR).Results: Prevalence of TNBC were 82.5% of basal-like subjects and 17.5% of non-basal-like subjects. Among the TNBC subjects, median age of each subtype was 50 years of basal-like subtype and 45 years of non-basal-like subtype. Both subtypes were mostly found in the subjects who aged >40 years. Higher histopathological grade was discovered in both subtypes. The therapy mostly carried out to the subjects was adjuvant chemotherapy. Majority of basal-like subtype subjects were still alive and had longer survival rate and lower incidences of deaths when compared to the non-basal-like subtype.Conclusion: In TNBC, the basal-like subjects showed greater median age, lower severity stage, and longer survival rate than the non-basal-like subjects. There was no histopathology grade between both subtypes. Keywords: Basal-like and non-basal-like subtypes, breast cancer, characteristics, triple negative